The Lao Economy: Capitalizing on Natural Resource Exports - Jayant Menon; Peter Warr (Asian Development Bank (ADB), 2013)
Trade and investment reforms in the Lao People's Democratic Republic (Lao PDR) since the mid-1980s have boosted natural resource-based exports, underpinning recent economic growth. A high proportion of the proceeds from these exports accrue directly to the government. Over the 8 years preceding 2011, total government revenue increased from 11% to over 19% of gross domestic product, due almost entirely to revenues derived from mining and hydropower. The effect on the Lao people depends on how the government uses these revenues. This paper examines how the Lao PDR's export-led growth can be channeled into directions that deliver the greatest benefit to the Lao people.
hdl:11540/2335
Keywords: O13; O24; Q37; 330; Lao PDR; natural resource revenues; Dutch disease; trade and investment reforms; Rohstoffreichtum; Handelsliberalisierung; Wirtschaftswachstum; Laos